Pan-Africanism or Pragmatism : Lessons of the Tanganyika-Zanzibar Union. - Shivji, Issa G. (Mkuki na Nyota Publishers, 2008)
The Pan-Africanist debate is back on the historical agenda. The stresses and strains in the union of Tanganyika and Zanzibar since its formation some forty years ago are not showing any sign of abating. Meanwhile, imperialism under new forms and labels continues to bedevil the continent in ever-aggressive, if subtle, ways. The political federation of East Africa, which was one of the main spin-offs of the Pan-Africanism of the nationalist period, is reappearing on the political stage, albeit in a distorted form of regional integration. It is in this context that the present study is situated.